Merajut Asa Melalui Program Kampus Mengajar 2: Reboisasi di Lingkungan SDN Pengengat - Tedy Zulkipli; M. Nazir Maulana; Husnul Khotimah; Heri Setiawan (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2024)
In order to overcome and overcome learning loss, especially in elementary schools, the Indonesian Ministry of Education and Culture is implementing the Teaching Campus program. Pengengat Elementary School, District. Pujut, Kab. Central Lombok, West Nusa Tenggara is one of the schools targeted for implementing the 2nd teaching campus in 2021. One of the programs implemented by the Pengengat 2nd Elementary School teaching campus team is reforestation. The method of implementing this service activity is carried out through 3 stages, namely planning, preparation and implementation. The activity was held on Saturday 16 October 2021. This activity was attended by KM2 students, students, teachers and the community around the school. The activity was carried out well and it is hoped that planting trees in the school environment can increase students' comfort while studying. Apart from that, it is hoped that students will have the character of being responsible for caring for the land, ammm and love for the surrounding environment.